Isolation and phylogenetic characterization of arboviruses circulating among phlebotomine sandflies in parts of North Rift, Kenya - Koskei, E.; Langat, S.; Mutisya, J.; Mulwa, F.; Lutomiah, J.; Koka, H.; Oyola, Samuel O.; Waihenya, R.; Mabeya, S.N.; Sang, R. (Frontiers Media, 2024)
Background: Until recently, arbovirus surveillance is mainly focused on mosquito and tick vectors, resulting in the discovery of several mosquito- and tick-borne arboviruses. However, the role of sandflies in arbovirus transmission and disease has remained largely unexplored. This study sought to isolate and characterize arboviruses from phlebotomine sandflies from selected pastoral ecozones in the North Rift region of Kenya.